Original paperImage guided adaptive brachytherapy for cervical cancer: dose contribution to involved pelvic nodes in two cancer centers - Bos, Willemien van den; Beriwal, Sushil; Velema, Laura; Leeuw, Astrid A.C. de; Nomden, Christel N.; Jürgenliemk-Schulz, Ina-M. (Journal of Contemporary Brachytherapy, 2014)
Purpose: The goal of this study was to determine the dose contributions from image guided adaptive brachytherapy (IGABT) to individual suspicious pelvic lymph nodes (pLNN) in cervical cancer patients. Data were collected in two cancer centers, University of Pittsburgh Cancer Institute (UPCI) and University Medical Center Utrecht (UMCU). Material and methods: 27 and 15 patients with node positive cervical cancer treated with HDR (high dose rate) or PDR (pulsed dose rate)-IGABT were analyzed. HDR-IGABT (UPCI) was delivered with CT/MRI compatible tandem-ring applicators with 5.0-6.0 Gy × five fractions. PDR-IGABT (UMCU) dose was delivered with Utrecht tandem-ovoid applicators with 32 × 0.6 Gy × two fractions. Pelvic lymph nodes with short axis diameter of ≥ 5 mm on pre-treatment MRI or PET-CT were contoured for all BT-plans. Dose contributions to individual pLNN expressed as D90 (dose to 90% of the volume) were calculated from dose-volume histograms as absolute and relative physical dose (% of the reference dose) for each fraction. For each node, the total dose from all fractions was calculated, expressed in EQD2 (equivalent total dose in 2 Gy fractions). Results: Fifty-seven (UPCI) and 40 (UMCU) individual pLNN were contoured. The mean D90 pLNN was 10.8% (range 5.7-25.1%) and 20.5% (range 6.8-93.3%), respectively, and therefore different in the two centers. These values translate into 2.7 Gy (1.3-6.6 Gy) EQD2 and 7.1 Gy (2.2-36.7 Gy) EQD2, respectively. Differences are caused by the location of the individual nodes in relation to the spatial dose distribution of IGABT, differences in total dose administered and radiobiology (HDR versus PDR). Conclusions : The IGABT dose contribution to individual pelvic nodes depends on patient and treatment related factors, and varies considerably.